1978
DOI: 10.1073/pnas.75.5.2483
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of membrane potential, an immediate effect of colicin K.

Abstract: (2), and inhibition of several active transport systems (3-6). Uptake and respiration of glucose remain normal, as do retention of a-methyl glucoside and facilitated diffusion of flD-galactosides (2).Previous experiments have shown that some of the observed changes are secondary effects (7). The processes that seem to be directly affected are those that are presumed to be dependent on an "energized membrane state." According to Mitchell's chemiosmotic hypothesis (8,9), the energized membrane state is identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Among the bacterial poreforming proteins, perhaps most noteworthy are the colicins secreted by bacteria. Colicins El, Ia, and K depolarize E. coil (38)(39)(40), and colicin K is known to create voltage-dependent channels in the planar bilayer membrane (23). This change in ion permeability induced by colicins is compatible with a single-hit killing mechanism for target bacteria (23,33).…”
Section: Pore-forming Protein From E Tlistolyticamentioning
confidence: 99%
“…Among the bacterial poreforming proteins, perhaps most noteworthy are the colicins secreted by bacteria. Colicins El, Ia, and K depolarize E. coil (38)(39)(40), and colicin K is known to create voltage-dependent channels in the planar bilayer membrane (23). This change in ion permeability induced by colicins is compatible with a single-hit killing mechanism for target bacteria (23,33).…”
Section: Pore-forming Protein From E Tlistolyticamentioning
confidence: 99%
“…Colicin El is a 522-residue bactericidal protein, known to exert its lethal effect through an ability to depolarize the cytoplasmic membrane of sensitive Escherichia coli (1)(2)(3). Studies of colicin El action using artificial membranes have shown that the deenergization results from an ion channel formed by the colicin molecule, which dissipates the cellular membrane potential (ref.…”
mentioning
confidence: 99%
“…Transmembrane potential (Em) generally reflects the functional integrity and metabolic state of the cell. Alterations in Em are often the initial response to metabolic poisons (Weiss and Luria, 1978;Okada et al, 1980) or membrane modifiers such as lipids (Boonstra et al, 1982). Cone (1970) has proposed that Em is the regulator of mitosis in both normal and neoplastic cells, with depolarization initiating proliferation and polarization causing the cessation of growth.…”
mentioning
confidence: 99%